A Review of Forest Management Effects on Terrestrial Leaf Litter Inhabiting Arthropods - Jess Hartshorn (Forests, 2021)
Leaf litter arthropods are some of the most abundant and diverse communities in forests and provide myriad ecosystem services from decomposition and mineralization to pollination and predation. They are important to forest health and management and, in turn, are affected by how we manage our forests. Various forest management techniques such as clear cutting, burning, and chemical control of invasive species all have differing effects on ground dwelling arthropods and, despite their importance, a review of the literature on these effects does not currently exist. My objective with this paper is to review the effects of different types of forest management on arthropods in leaf litter systems.